Effect of sterilization treatment on polyphenol content, antioxidant activity and stability of free and encapsulated herb (Terminalia arjuna) added milk drink - Sawale, Pravin; Patil, Girdhari Ramdas; Hussain, Shaik Abdul; Singh, Ashish Kumar; Singh, Ram Ran Bijoy (Indian Journal of Dairy Science, 2019)
In the current investigation, effect of heat treatment(121ºC/15 min) on stability, polyphenols content and antioxidantactivity of milk drinks added with alcoholic extract Terminaliaarjuna were determined. Four different vanilla chocolate flavouredmilk drink samples viz. supplemented with free (Drink 1) andencapsulated (Drink 2) form of T. arjuna and their respectivecontrols (Control 1 & Control 2) devoid of herbal extract wereprepared. The sterilization treatment reduced the antioxidantactivity and phenolic content of drink 1, while reverse trend wasnoticed for drink 2. Heat coagulation time, measure of stability ofmilk drinks, revealed that addition of T. arjuna extract led to adecrease in pH (Drink 1 – pH 6.67 to 6.65 and Drink 2 –pH 6.67 to6.66) of milk drinks thus led to destabilization of casein micellesas evidenced from the appearance of flakes in heat stability tubes.Control samples showed type A kind of HCT-pH profile, whileDrink 1 and Drink 2 showed type B kind of HCT-pH profile. Thestudy indicated that encapsulation is effective in preserving thebioactivity of T. arjuna extract during heat treatment.